Music entrepreneurship - Dumbreck, Allan; McPherson, Gayle, 1968- (London : Bloomsbury Methuen Drama, 2016)
The music industries hinge on entrepreneurship. The recent, rapid convergence of media and the parallel ongoing evolution of music businesses have again seen the focus shift to independent companies and individual entrepreneurs. Opportunities tend not to be advertised in professional music and practically everyone begins on their own: forming a band, starting a record label, running events, or building a website. But it's not an easy territory to navigate or get a handle on. Music Entrepreneurship features an analysis of the changing landscape of the music industries and the value of the entrepreneur within them through a series of focused chapters and case studies. Alongside contributions from key academics across the globe, expert contributors from across the industry highlight successful entrepreneurs and offers practical help to the reader trying to navigate the business. Sectors examined include: The value of the music industries Recorded music Live events Branding in music Artist management Digital distribution.
Web 3.0 and digital music distributionIndependent artists as prosumers: Tools for digital distribution; The digital distribution landscape; Sector overview; Digital aggregators; Digital retailers; Streaming services; New developments: Tidal; Subscription services; Crowdfunding platforms; Digital content management platforms; Case study: EmuBands (Ally Gray); Case study: Jessica Carmody (Account Manager at PledgeMusic UK); 'I'm not an entrepreneur': A British perspective?; References; Websites; 9 Music Publishing: How to Understand and Engage with Copyright in the Digital World; Introduction.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed December 2, 2015).
eBooks on EBSCOhost
Keywords: Music trade; Music -- Economic aspects; Entrepreneurship; Entrepreneurship; Musique -- Industrie; Musique -- Aspect économique.; Entrepreneuriat; entrepreneurs; MUSIC -- Genres & Styles -- Classical; MUSIC -- Reference; Entrepreneurship; Music -- Economic aspects; Music trade